KEARIFAN LOKAL KMOT AYA SUKU MAYBRAT DALAM MELESTARIAKAN SUMBER AIR DI KAMPUNG KAMISABE DAN KAMPUNG MOS DISTRIK MOSWAREN KABUPATEN SORONG SELATAN - Way, Anike; Sinaga, Nurhaidah; Warami, Hugo (Universitas Papua, 2018)
This study aims to identify the application forms of kmot aya to support the water resources conservation, to know the application mechanism of kmot aya and to know the application implication of kmot aya as supporting thewater resources conservation. The study was conducted at Kamisabe and Mos Villages in Sorong Selatan Regency for approximately two months (August to September 2017). A total of 34 respondents were used in this study. There are two water sources that are still used by the community, there are Wor River controlled by Athabu Family at Kamisabe village and Sisyah River controlled by Homer family at Mos village. Both the water sources are still preserved. This is because the Maybrat tribe have local wisdom that has been passed down from generation to generation from their ancestors known as Ã¢Â€Âœkmot ayaÃ¢Â€Â. Kmot aya contains values, beliefs and sanctions or rules to protect and conserve water resources. All respondents (100%) stated that kmot aya has been applied since their ancestors. In addition, the majority of respondents (50%) stated that the prohibition form in kmot aya banned bathing with soap and prohibited watering water without permission and sent by the natives of the region (Ra Tabam). While for the fine, the majority of respondents (76.47%) stated that the toughest punishment is a combination of money and wansafe cloth that can reach up to Rp. 1.2 billion. The water debit data shows that the Wor River has a larger water debit at 95,380.57 liters/sec, while the Sisyah River only hasa water debit at 14,249.55 liters/sec. The water temperature in the Sisyah River is at 22.20 oC in the morning and at 22.40 oC in the afternoon, while the Mor River is at 22.90 oC in the morning and at 22.00 oC in the afternoon. The results of odor and taste tests on both sources of water obtained that both water has no odor and also tasteless.